FORMATION OF PROFESSIONAL VALUES FUTURE TEACHER IN THE LEARNING PROCESS HUMANITIES - H.M. Udovichenko (Academy of Cognitive and Natural Sciences, 2008)
The article deals with some actual problems concerning the formation of a future teacher's professional values in the process of humanitarian subjects learning.